Under the radar – Exceptionally high environmental concentrations of the high production volume chemical sulfamic acid in the urban water cycle. (15th May 2020) - Freeling, Finnian; Scheurer, Marco; Sandholzer, Anna; Armbruster, Dominic; Nödler, Karsten; Schulz, Manoj; Ternes, Thomas A.; Wick, Arne
Abstract: Elevated concentrations of sulfamate, the anion of sulfamic acid, were found in surface waters and finished drinking water in Germany with concentrations up to 580 μg/L and 140 μg/L, respectively. Wastewater treatment plant (WWTP) effluent was identified as the dominant source of sulfamate in the urban water cycle, as sulfamate concentrations correlated positively (0.77 > r < 0.99) with concentrations of the wastewater tracer carbamazepine in samples from different waterbodies. Ozonation and activated sludge experiments proved that sulfamate can be formed from chemical and biological degradation of various precursors. Molar sulfamate yields were highly compound-specific and ranged from 2% to 56%. However, the transformation of precursors to sulfamate in WWTPs and wastewater-impacted waterbodies was found to be quantitatively irrelevant, since concentrations of sulfamate in these compartments are already high, presumably due to its primary use as an acidic cleaning agent. Sulfamate concentrations in the influent and effluent of studied WWTPs ranged from 520 μg/L to 1900 μg/L and from 490 μg/L to 1600 μg/L, respectively. Laboratory batch experiments were performed to assess the recalcitrance of sulfamate for chemical oxidation. In combination with the results from sampling conducted at full-scale waterworks, it was shown that common drinking water treatment techniques, including ozonation and filtration with activated carbon, are not capable to remove sulfamate. The results of biodegradation tests and from the analysis of samples taken at four bank filtration sites indicate that sulfamate is attenuated in the sediment/water interface of aquatic systems and during aquifer passage under aerobic and anaerobic conditions. Sulfamate concentrations decreased by between 62% and 99% during aquifer passage at the bank filtration sites. Considering the few data on short term ecotoxicity, about 30% of the presented sulfamate levels in ground and surface water samples did exceed the predicted no-effect concentration (PNEC) of sulfamate, and thus effects of sulfamate on the aquatic ecosystem of wastewater-impacted waterbodies in Germany cannot be excluded so far. Toxicological estimations suggest that no risk to human health is expected by concentrations of sulfamate typically encountered in tap water. Highlights: Sulfamate occurs almost ubiquitously in major surface waters in Germany. The predominant source of sulfamate in the urban water cycle is WWTP effluent. Sulfamate is a degradation product of various synthetic compounds. Common water treatment techniques are incapable to remove sulfamate. Results indicate attenuation of sulfamate during bank filtration.